2004
DOI: 10.2308/aud.2004.23.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Nonaudit Fees, Auditor Independence, and Bond Ratings

Abstract: participants of the Southeast AAA, and participants at the national AAA meeting in Hawaii for helpful comments and suggestions on previous drafts. We would also like to thank Mark DeFond (the Associate Editor) and two anonymous reviewers for comments and recommendations that have helped us to improve this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…For the empirical results, Law (2011) documents that the auditor in Hong Kong perceived non-audit services provision threats to their independence. Moreover, because of potential auditor independence issues, excess NAS fee will have an unfavorable effect on the bond rating (Brandon et al, 2004) and the creditability of financial statement (Krishnan et al, 2005).…”
Section: Additional Test -Family Firms and Non-audit Service (Nas) Feesmentioning
confidence: 99%
“…For the empirical results, Law (2011) documents that the auditor in Hong Kong perceived non-audit services provision threats to their independence. Moreover, because of potential auditor independence issues, excess NAS fee will have an unfavorable effect on the bond rating (Brandon et al, 2004) and the creditability of financial statement (Krishnan et al, 2005).…”
Section: Additional Test -Family Firms and Non-audit Service (Nas) Feesmentioning
confidence: 99%
“…Many researchers argue that it is not possible for this level of objectivity to be sustained (Brandon et al, 2004;Frankel et al, 2002;Glezen and Millar, 1985;Jenkins and Krawczyk, 2001;Lowe and Pany, 1995;1996;Raghunandan, 2003;Wines, 1994) because the auditors would in effect be auditing their own work, and perhaps acting in management role. The strong economic bond is believed to affect "their mental attitude, impartiality and objectivity, and independence of thought and act" (Flint, 1988:82), heightening the risk that auditors may surrender to management pressure when they provide ongoing NAS (Antle, 1984;Canning and Gwilliam, 1999;DeAngelo, 1981a;Magee and Tseng, 1990;Simunic, 1984).…”
Section: Arguments Against the Provision Of Non-audit Services (Nas)mentioning
confidence: 99%
“…The strong economic bond is believed to affect "their mental attitude, impartiality and objectivity, and independence of thought and act" (Flint, 1988:82), heightening the risk that auditors may surrender to management pressure when they provide ongoing NAS (Antle, 1984;Canning and Gwilliam, 1999;DeAngelo, 1981a;Magee and Tseng, 1990;Simunic, 1984). Indeed, Brandon et al (2004) found a negative relationship between the size of NAS fees paid to external auditors and a firm's bond rating.…”
Section: Arguments Against the Provision Of Non-audit Services (Nas)mentioning
confidence: 99%
“…Similar evidence is provided by Gul et al (2006) in the Australian market. With respect to market pricing of corporate debt, Brandon et al (2004) find that the amount of NAF received by the external auditor negatively affects the corporate bond ratings. Dhaliwal et al (2008) also provide evidence consistent with Brandon et al (2004).…”
Section: [Table 2 and Figure 2 About Here]mentioning
confidence: 99%